Interdisciplinary research as a form of monument protection and preparation for the investment process on the example of the former Gdańsk Shipyard complex - Orchowska-Smolińska, Anna; Kriegseisen, Anna; Szczepański, Jakub (Interdyscyplinarne badania jako forma ochrony zabytków i przygotowania do procesu inwestycyjnego na przykładzie zespołu dawnej Stoczni Gdańskiej, 2022)
The subject that is discussed in the article is a multidisciplinary study of a post-industrial building complex, which was carried out on the site of the former Gdańsk Shipyard. Its authors prove that in the case of complex objects of post-industrial heritage, the use of traditional schemes of description, assessment and valuation of a monument consisting in distinguishing primary and secondary materials for individual elements of the complex has serious limitations. Based on these experiences, the article presents a research model for an industrial complex that is a special example of a heritage site for which the oldest cultural layers do not constitute its greatest value. The authors of the article set themselves the goal of presenting the research method they created, based on strict adaptation to the specificity of the facility by means of, among others, recognition of the way it works, and especially the technological processes of the plant in the 1970s and 1980s, a period that had a special impact on the constitution of its status as an object of outstanding values. One of the procedures used in the research was the inclusion of specialists from the shipbuilding industry, historically associated with this particular industrial plant, in the work of the team. This allowed for a more complete identification of the resource in terms of technology and historically used production methods, as well as setting the framework for its protection and creating a conservation concept. The summary of the article presents the potential of using the presented research model in the design process on the example of an industrial facility prepared for the investment process (former Main Warehouse, the so-called U-Boat Hall).
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 103-115
Keywords: architektura; architectural and conservation documentation; conservation guidelines; colour pattern; adaptation of post-industrial monuments; Gdańsk Shipyard; dokumentacja architektoniczno-konserwatorska; wytyczne konserwatorskie; wzornik kolorystyczny; adaptacja zabytków poprzemysłowych; Stocznia Gdańska